Primary Language, Social Determinants of Health, and the Lived Patient Experience After Heart Transplantation: A Comparative Qualitative Study - Mansi K. Shah; Zara Latif; Carolina Lemos; Adi Hertz; Elena Donald; Byron Fuselier; Jordan Lindekens; Fabian Vargas; Afsana Rahman; Farhana Latif; Kevin J. Clerkin; Gabriel Sayer; et al. (Clinical Transplantation, 2026)
ABSTRACT Background Over 4,500 individuals undergo heart transplantation (HT) in the United States every year. Limited qualitative data exist evaluating challenges and barriers in the evaluation and post‐transplant process and their association with primary language spoken. Methods We conducted semi‐structured interviews with individuals who received HT at a high‐volume urban academic medical center between 2015 and 2024. Primary English and Spanish speaking patients were included; interviews were conducted by a certified Spanish speaker. Interviews were audio‐recorded and transcribed for thematic analysis. Themes were compared based on primary language spoken. Results 34 HT recipients (median age 61 years, 38% women) participated in this study. Forty‐one percent ( n = 14) identified Spanish as their primary language. Three key thematic differences emerged based on primary language spoken: (1) perception of the transplant process and emotional needs, (2) financial concerns while awaiting transplant, and (3) methods of communication. Spanish speaking patients more commonly relied on family support, faith, and public assistance programs to navigate the transplant process. English speaking patients, on the other hand, more frequently struggled with the morality of accepting a transplant. Additionally, English speaking patients more commonly had increased financial resources, highlighting the intersection with education and other social determinants of health (SDOH). Conclusion This study identifies key differences in the experiences of HT recipients based on the patient's primary spoken language and inter‐related SDOH. This study can inform future studies focused on the impact of health policy changes and the expansion of social support systems on transplant allocation among linguistically diverse communities.